Sustainable Forage Production in Crop–Livestock Systems - Renata La Guardia Nave (Agronomy)
This Special Issue, “Sustainable Forage Production in Crop–Livestock Systems”, explores the urgent need for diversified and sustainable farming practices, focusing on the integration of crop and livestock systems to enhance economic resilience, ecological health, and environmental sustainability [...]